10.1016/s1558-0164(06)70223-1 (CrossRef Listing of Deleted DOIs, 2000)
Objectives To examine system-level changes in influenza vaccination coverage in residential aged care homes (RACHs) following the introduction of the Aged Care On-site Pharmacist (ACOP) funding initiative, and to explore the experiences of RACH managers and pharmacist immunizers. Methods A convergent mixed methods study was conducted in the Hunter New England Local Health District (HNELHD), Australia. Publicly available Australian Immunization Register (AIR) influenza vaccination coverage data for RACH residents were compared at baseline (June 2024) and one-year post-ACOP implementation (August 2025). Semi-structured interviews with RACH managers (n = 10) and pharmacist immunizers (n = 12) explored experiences of vaccination delivery and ACOP implementation. Quantitative and qualitative data were analyzed separately and integrated during interpretation. Results The proportion of RACHs achieving ≥ 80% influenza vaccination coverage increased from 29% in 2024 to 64% in 2025. However, attribution to ACOP alone was not possible, and variability in implementation was evident. Five key themes were identified in the semi-structured interviews: (1) strengthening partnerships to improve vaccination in aged care, (2) enhancing workflow and vaccination through access to an on-site pharmacist, (3) overcoming operational and logistical barriers, (4) access to comprehensive data, and (5) funding issues impacts sustainability. Conclusions A system-level increase in influenza vaccination coverage occurred following introduction of funding to ACOPs providing immunization services in RACHs. Qualitative findings suggest embedded pharmacists may strengthen vaccination coordination, data monitoring, and multidisciplinary collaboration within aged care. Sustainable funding, role clarity and improved data systems are essential to maintain these gains.